Effectiveness of jigsaw, think-pair-share and numbered heads together on students' oral participation in speaking lessons - Nguyễn, Thị Thu Thủy (University of Languages and International Studies, 2017)
The study is aimed at finding feasible ways to enhance the first year English major students'oral participation in English speaking classes at Hanoi Pedagogical University No.2-an intermediate step to improve the students' English proficiency. To gain that aim, the study investigates the causes of students' poor participation in speaking lessons and proposes three cooperative techniques including Jigsaw, Numbered heads together and Think-pair-share as the treatment. Therefore, the effectiveness of those three techniques on students' participation is the main variable under examination.